An analysis of trace element by atomic absorption in samples of human milk collected in Amapá’s Bank of Milk - Danilo Monteiro Monteiro; Roberto Bezerra Messias (O Mundo da Saúde)
This work evaluated the concentration of minerals in milks which are donated to the Bank of Milk of Amapá State, by means of the technique of atomic absorption, with the aim to argue for the importance of this analysis in the routine of Banks of Milk do as to help in therapeutic treatments of newborn babies who have lack of some minerals. After quantifying these levels, the milk could have been used for therapeutic treatments for infants who have a certain mineral deficiency. Quantitative analysis of the elements presents in milk focused on Ca, Cu, Zn, Mg, Mn, Na, Cd, Fe, Pb and K. These elements were chosen because of their importance and nutritional value for absorption by newborns, as well as those that may cause acute intoxication, for example, Cd and Pb, which are common at low levels in certain foods and drinks. For example, in a milk sample a content of 1 ppm Cd was found, thereby being an average value of contamination. The results of the analysis were divided into 4 zones, representing the collection points in state Amapá. In two zones we observed high levels of Mn and Na. And, checking all points of the study, it was found that the tests were satisfactory, particularly as regards comparisons to similar tests for atomic absorption and commercial brands. Anyway, it was observed in this study that the investigative method of metals in human milk is of paramount importance so as to be recommended as a routine part of Milk Banks, especially for therapeutic and nutritional ends, by analyzing the quality and quantity of constituent elements of such milks